The definitive guide to emergency department operational improvement : employing Lean principles with current ED best practices to create the "no wait" department - Crane, Jody; Noon, Chuck (Chuck E.) (New York : Productivity Press, 2019)
This revised and updated book explores the academics behind managing the complex service environment that is the Emergency Department (ED) by combining applied management science and practical experiences to create a model of how to improve operations. This book offers a presentation of Lean tools used in the ED along with basic and advanced flow principles. It then shows how these concepts are applied and why they work, supported by case studies in which Lean principles were used to transform an underperforming ED into a world-class operation. After reviewing best practices, the authors explain how to achieve excellence by discussing the elements of creating a culture of change.
Previous edition: 2011.
OCLC-licensed vendor bibliographic record.
Keywords: Hospitals -- Emergency services -- Administration; BUSINESS & ECONOMICS / Quality Control; BUSINESS & ECONOMICS / Industries / Manufacturing Industries; BUSINESS & ECONOMICS / Industries / Service Industries